The Influence of Teachers’ Communication Skills and the Learning Environment on Learning Motivation - Manongko, Allen Ch.; Momongan, Jeremy F.; Rattu, Febriani M.L. (Universitas Muhammadiyah Sumatera Utara (UMSU), 2025)
This study aims to analyze the influence of teachers’ communication skills and the learning environment on students’ learning motivation at SMK Swasta Poopo Bolmong. The research employed a quantitative approach with an ex post facto design, where the researcher did not provide direct treatment but examined the relationships among variables based on existing data. The sample was determined through proportional random sampling, and the research instrument was a Likert-scale questionnaire covering three main variables: teachers’ communication skills, learning environment, and students’ learning motivation. The results indicate that teachers’ communication skills have a positive impact on students’ learning motivation. Teachers who are able to deliver material clearly, coherently, and engagingly can enhance students’ attention and interest in the learning process. Furthermore, a supportive learning environment, both physically and psychologically, plays an important role in encouraging students to be more enthusiastic and motivated in their studies. Simultaneously, teachers’ communication skills and the learning environment complement each other in shaping students’ learning motivation. This finding is consistent with learning motivation theory, which emphasizes that internal and external factors must interact synergistically for students to achieve optimal learning outcomes. The practical implication of this study is the need to improve teachers’ communication skills and to develop a supportive learning environment so that students’ learning motivation can grow sustainably.